Review of current asset maintenance in South African ports and recommendations for smart port maintenance - Mthembu, Phumelele (Department of Civil Engineering, 2025)
Transnet National Ports Authority's (TNPA's) waterside infrastructure is key to facilitating safe port navigation and operations in South Africa. Conflicting information regarding the asset condition of TNPA's infrastructure provides a need for objective asset condition assessments and ratings using international guidelines and standards. This qualitative research reviews the condition assessment guidelines prescribed in the TNPA Asset Maintenance Principles and Procedures (AMPP) Manual for waterside infrastructure. The research aims to understand the current challenges experienced with the asset condition assessments, evaluate the effectiveness of the condition assessment methods in assessing chloride-induced deterioration and evaluate how smart port maintenance can benefit TNPA. The Port of Cape Town's condition assessment data for waterside infrastructure, collected between 2020 and 2023, is used as a case study for this research. The literature review discusses concrete structures in the marine environment in terms of their exposure conditions, durability, service life prediction and effective tests to assess chloride induced deterioration. The benefits of smart port maintenance technology are explored using case studies from international ports such as the Hamburg Port Authority (HPA) in Germany and Norvic Port in Sweden. Insights are provided on how Digital Twin (DT) models can autonomously make maintenance decisions and improve maintenance strategies. The methodology adhered to is informed by guidelines from the World Economic Forum's Strategic Infrastructure Report to assist governments and key stakeholders in developing comprehensive frameworks for the operation, maintenance and end-of-lifecycle decisions of existing infrastructure. Existing literature, TNPA data and case studies are used for the observations and recommendations. The main steps include conducting a status quo analysis of the current condition assessment methods and a benchmarking analysis which includes leveraging technology to improve maintenance in ports. The four condition assessment methods used in TNPA to assess waterside infrastructure consist of the eyeball inspection, aerial survey, instrument measure and diving inspection methods. The observations found that the current asset condition ratings for TNPA's waterside infrastructure are based on incomplete condition assessment methods which do not effectively assess chloride-induced deterioration. A recommendation is suggested to include cover assessments, delamination surveys and measurements of half-cell potential, corrosion rate and resistivity as part of the condition assessment methods with revised frequencies. Chloride profiling and service life prediction models are recommended to predict the remaining service life. A standardised asset condition guideline, which is aligned with the size of concrete defects, is also recommended for objective asset condition ratings. To leverage technology, TNPA's current Systems, Applications, and Products in Data Processing (SAP) Plant Maintenance (PM) software is compared to smart technology used by international ports. The main limitation of the SAP PM software is its ability to only track and manage maintenance activities. DT technology is recommended due to its ability to diagnose the deterioration of port infrastructure and improve maintenance strategies. To implement DT technology in TNPA, the main enablers required include the installation of sensors which detect and diagnose deterioration and the use of Building Information Modelling (BIM) software. Limitations of implementing DT technology such as high costs, data security risks and the lack of standards and frameworks should be taken into account. Considering these implementation barriers, TNPA can currently ensure that inputs to the SAP PM software are informed by the recommendations provided in this research.